Design and Analysis of a Hybrid Composite-Steel Frame Chassis for a Small Racecar - Nurzaki Bin Ikhsan, Nurzaki (Universiti Teknologi Petronas, 2008)
This dissertation includes an overview of the Final Year project. The title is “Design and Analysis of a Hybrid Composite-Steel Frame Chassis for a Small Race-car” this project will collaborate with the Formula SAE competition. This dissertation contains the objective of the project, scope of the study and problem statement. There is also a methodology part which is will explain about the step and method during designing and analysis the chassis. Beside, this dissertation also provides a literature review that’s consisting of the previous work or project done by other personnel that have similarity with the project proposed and also contain information and theory about the project and done by collecting it from various sources available such as journal, book and internet. The chassis was going through the side impact and longitudinal stiffness analysis as it result the improvement from the previous chassis design. The goal of this project is to design and analysis a new hybrid composite –steel frame chassis. The idea is to design a monocoque chassis that optimize the chassis strengthmass ratio. This design also will be limited to Formula SAE rules.